Bendera Macan Ali Koleksi Museum Tekstil Jakarta - Haris, Tawalinuddin (Paradigma: Jurnal Kajian Budaya, 2010)
The Textile Museum of Jakarta in Tanah Abang preserves a ragged animal calligraphy embroidered in indigo banner framed in white silk cloth of the Cirebon Sultanate made in 1797. The old bunting has three pictures of “Ali” Tiger painted in Arabic letters, a double-edged Sword of Zulfakar, four magical square boxes decorated with Arabic inscription, and Arabic letters quoted from the Quran on five-cornered stars. The paper describes the significance of the regalia: it does not only function as the symbol of sovereignty of the Cirebon Sultanate, but it also has a magical power to protect the kingdom.